Monitoring and Control of Particulate Matter in Urban Area in Douala-Cameroon Town - Severin Mbog Mbog; Cyrille Adiang Mezoue; Yannick Cédric Ngangmo; Dieudonné Bitondo; Ruben Martin Mouangue (Advances in Meteorology)
This study focused on the content of fine particle air pollution in the city of Douala. Several studies have analyzed pollution problems due to road traffic in Douala, Cameroon. Particle concentration levels are higher in heavy traffic than in light traffic. The population’s exposure to air pollution in cities is higher near roads. Several studies have analyzed pollution problems due to road traffic in Douala, Cameroon. In this city, the traffic density at the intersections is indeed higher. Thus, the question is as follows: Are these traffic areas hotspots of increased PM exposure levels? To determine it, four particle size fractions (PM10, PM2.5, PM5, and PM1) were collected using an “OC300 Gas and Dust Particle Laser Detector” for three months at different traffic locations (roundabouts or/and crossroads). Statistical analysis of the data shows very high concentrations at most measurement sites. PM concentrations at the different measurement sites are around 35.69-68.08 µg m−3 for PM1, 50.72-99.13 µg m−3 for PM2.5, 54.11-111.22 µg m−3 for PM5, and 57.97-119.25 µg m−3 for PM10. Exceedances of WHO daily guidelines for PM2.5 (45 µg m−3) and PM10 (15 µg m−3) were found during the measurement campaign, indicating that crossroads are the pollution hotspots in urban areas. Occupation of the roadsides for various economic activities (painting, restaurants, donut shops, etc.) is common in Cameroon, increasing health risks for people working around the roadside. Thus, crossroad locations are areas where the level of exposure to PMx is the highest on road traffics.